Print Culture at the Crossroads
1 online resource.
Keywords: Print Culture at the Crossroads investigates how the spread of printing shaped a distinctive literary culture in Central Europe during the early modern period. Moving beyond the boundaries of the nation state, twenty-five scholars from over a dozen countries examine the role of the press in a region characterised by its many cultures, languages, religions, and alphabets. Antitrinitarians, Roman and Greek Catholics, Calvinists, Jews, Lutherans, and Orthodox Christians used the press to preserve and support their communities. By examining printing and patronage networks, catalogues, inventories, woodblocks, bindings, and ownership marks, this volume reveals a complicated web of connections linking printers and scholars, Jews and Christians, across Central Europe and beyond.